Immunoprophylaxis and therapy of grafted rat colonic carcinoma. Issue 3 (March 1977) - Martin, M S; Martin, F; Justrabo, E; Michel, M F; Lagneau, A
Abstract : Two independent lines of chemically-induced colonic carcinoma, serially graftable in syngeneic rats, have been used to investigate the effects of immunoprophylaxis and immunotherapy. Rats were immunised by various procedures, including BCG, irradiated tumour grafts, and cancer cells treated by mitomycin and neuraminidase. A partial inhibition of tumour growth was observed in one of the four protocols. On the other hand, a significant enhancement of tumour growth was obtained in two other experiments.